Surgical excision of a giant cardiac fibroma in an asymptomatic child - Seçici, Serkan; Uysal, Fahrettin; Yazıcıoğlu, Volkan; Bostan, Özlem Mehtap; Şenkaya Sığnak, İşık (The European Research Journal, 2018)
Cardiac fibroma is a rare primary tumor of the heart. Patients can be asymptomatic or present with palpitations, cardiac murmur, syncope, arrhythmias, symptoms of congestive heart failure, or sudden death. We report a case of successful surgical excision of a giant cardiac fibroma in an asymptomatic child.